Sensitivities of Various Electrophysiological Methods in the Diagnosis of Ulnar Neuropathy at the Elbow - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
Aim: To determine the sensitivities of electrophysiological tests in patients with ulnar nerve compression at the elbow. Methods: The study was conducted on 21 patients (33 arms) with symptoms and signs of ulnar neuropathy and 20 healthy individuals. All cases were investigated with ulnar nerve motor, sensory, mixed, long and short segment motor conduction studies, and needle electromyography. All motor conduction studies were performed separately from abductor digiti minimi (ADM) and first dorsal interosseous (FDI) muscles. Results: The sensitivities of electrophysiological tests including ulnar nerve sensory latency (24%), ulnar mixed conduction velocity (61%), conventional 10 cm segment elbow conduction velocity recorded over ADM (61%), conventional 10 cm segment elbow conduction velocity recorded over FDI (70%), ulnar nerve F response latency recorded over ADM (42%), ulnar F latency recorded at FDI (55%) were found in a wide range, and it is 100% for short segment motor conduction in elbow recorded from both the ADM and FDI. Conclusions: Long segment ulnar nerve motor and ulnar sensory nerve conduction studies have relatively lower sensitivity than short segment ulnar motor and mixed nerve conduction studies. Therefore short segment motor or mixed studies of ulnar nerve should routinely be performed to prevent under diagnosis. Key Words: electromyography, short segment nerve conduction studies, mixed nerve conduction study, ulnar neuropathy at the elbow
Keywords: electromyography; short segment nerve conduction studies; mixed nerve conduction study; ulnar neuropathy at the elbow; SEGMENT NERVE-CONDUCTION; LOCALIZATION